A música como arte : significação musical e a ontologia da obra de arte de Arthur C. Danto - Henrique Iwao Jardim da Silveira (2023)
The present thesis starts from Arthur C. Danto's ontology of the work of art, developed mainly in his book The Transfiguration of the Commonplace. It considers that music is one of the arts and that as such it is capable of producing works of art. Thus, we should be able to characterize musical works according to Danto's ontology, if that theory is consistent. Given the importance, for Danto, of the idea of embodied meaning and correlates, considerations about the meaning of musical works and the role of exemplification are made (Chap. 1). The idea of the artworld is then addressed; that of the musicworld is formulated (Chap. 2). The idea of indiscernible and Danto's important method of indiscernibles are then investigated. This study leads to thoughts about the relationship between art/music and life (Chap. 3). The exemplary and revelatory role, for Danto's theory, of Andy Warhol's Brillo Box, is compared with that of John Cage's 4'33", in the musical sphere (Chap. 4).